STRENGTHENING SME FOOD PRODUCTS THROUGH PRODUCT PACKAGING TRAINING - Mardalena, Mardalena; Hidayat, Ariodillah; Andaiyani, Sri; Liliana, Liliana; Wulandari, Zulfa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
The training includes introducing the concept of packaging, the benefits of packaging, packaging design, and making packaging product. Kemplang crackers, Rengginang, Chips, and Pempek are commodities produced by the SMEs assisted by the PPMK in Prabumulih City. However, the packaging is inadequate so that it is not feasible to be marketed to a wider market such as minimarkets, hotels, or other modern markets. The result of this training is that participants understand the importance of adequate packaging so the product has value-added and can increase product competitiveness. Participants become skilled in packaging after packaging practice. We recommend that the training program for packaging craft products be continued by providing packaging tools so that more groups of craftsmen can experience the benefits. The training participants are expected to be able to take an active role in improving the quality of the product and pass the knowledge they have gained to other craftsmen in their area.